Eosinophilic pustular folliculitis associated with IgA deficiency - L. E. Flowers; S. Subhadarshani; S. Quinter; C. Shaughnessy (JEADV Clinical Practice)
Abstract Eosinophilic pustular folliculitis (EPF) is a noninfectious follicular based inflammatory dermatosis. We present a case of a 57‐year‐old female of Indian ethnicity who developed a pustular eruption, with certain lesions displaying Koebnerization. Given that the morphologic distribution most represented the immunosuppressant EPF subtype, additional testing led to the discovery of concurrent IgA deficiency. This case highlights a particularly unusual presentation of EPF associated with IgA deficiency and Koebner phenomenon.